The Effect of Taxes on Corporate Financing Decisions - Evidence from the German Interest Barrier - Alberternst, Stephan; Sureth-Sloane, Caren
The literature suggests that when taking tax effects into account, debt ought to be prefer-able to equity. Thus, with all else being equal, levered firms are expected to show higher firm values.However, there are no uniform predictions of the size of this tax benefit from interest deductibility nor on the effect of changes in interest deductibility. We believe that the German corporate tax re-form in 2008, which introduced an interest barrier, can serve as a promising “quasi-experiment” to investigate the effects from a reform of interest deductibility. A study of this reform on the basis of German financial statement data is of general interest because, first, similar interest barriers have been introduced in several countries and proposed by the OECD to fight BEPS. Second, the major characteristics of the German tax system can be regarded as representative for most European and major Asian countries. Third, single entity financial statements for German companies allows us to capture tax and capital structure details that have not been available in most prior studies. With significance at the 5% level, we find evidence that the companies that are affected by the interest barrier reduce their leverage by 4.7 percentage points more than companies that are not affected by the interest barrier. We are the first to employ a detailed matching approach to the underlying rich dataset, which enables us to overcome several limitations of previous studies. Our results imply that capital structure reactions most likely have been underestimated in previous studies.

Uncertainty in Weighting Formulary Apportionment Factors. How Does Weighting Uncertainty Impact After-Tax Income of Multinational Groups?, - Ortmann, Regina
Formulary apportionment is an intensively debated mechanism for allocating tax base within multinational groups. Systems under which the formula is identical in all jurisdictions and systems under which jurisdictions can determine the weights on the formula factors individually can be observed. The latter systems produce uncertainty about the overall tax-liable share of the future group tax base. Counter-intuitively, I identify scenarios under which increased uncertainty leads to higher expected future group income. My results provide helpful insights for firms and policy makers debating the specific design of a formulary apportionment system.

Entscheidungskalküle US-amerikanischer Unternehmen bei Tax Inversions. What Drives the Decision of U.S. Firms to Expatriate? - Oßwald, Benjamin; Sureth-Sloane, Caren (Steuer und Wirtschaft International)

Investment Effects of Wealth Taxes under Uncertainty and Irreversibility - Niemann, Rainer; Sureth-Sloane, Caren

Mehr Theorie wagen: Eine neue Ausbildung für die Praxis? - Sureth, Caren (WiSt - Wirtschaftswissenschaftliches Studium)

Does mandatory IFRS adoption facilitate debt financing? - Florou, Annita; Kosi, Urska (Review of Accounting Studies)
We examine whether the mandated introduction of International Financial Reporting Standards (IFRS) is associated with the propensity to access the public rather than private debt market and the cost of debt. We use a global sample of public bonds and private loans and find that mandatory IFRS adopters are more likely, post-IFRS, to issue bonds than to borrow privately. We also find that mandatory IFRS adopters pay lower bond yield spreads, but not lower loan spreads, after the mandate. These findings are consistent with debt providers responding positively to financial reporting of higher quality and comparability, but only when there is a greater reliance on publicly available financial statements than private communication. Lastly, we document that the observed debt market benefits are concentrated in countries with larger differences between domestic GAAP and IFRS and are present even for EU countries that did not experience concurrent financial reporting enforcement or other institutional reforms. Overall, our study documents positive economic consequences around the mandated IFRS adoption for corporate debt financing and, in particular, for bond financing.
Keywords: Accounting regulation; IFRS; Accounting quality; Public and private debt markets; Cost of debt

Vermögensteuer und ihre Implikationen für den Wirtschaftsstandort Deutschland - eine betriebswirtschaftliche Analyse - Hoppe, Thomas; Maiterth, Ralf; Sureth-Sloane, Caren
Die (Wieder-)Einführung einer Vermögensteuer ist in den vergangenen Jahren erneut in den Fokus der politischen Diskussion gerückt. Der vorliegende Beitrag vermittelt einen Eindruck von den Belastungswirkungen, die aus der Umsetzung von aktuell vorliegenden Besteuerungskonzepten resultieren würden. Auf der Basis von realen Jahresabschlussdaten wird eine mehrperiodige Veranlagungssimulation durchgeführt, die insbesondere ermöglicht, den zu erwartenden Eigenkapitalverzehr sowie den Anstieg der Steuerbelastung für die betrachtete Unternehmensgruppe zu quantifizieren. Von besonderem Interesse sind hierbei Unternehmen deren laufende Erträge nicht ausreichen, um die Belastungen durch die Vermögensteuer zu tragen und damit einem Substanzverzehr ausgesetzt sind. Es zeigt sich, dass etwa die Hälfte der Unternehmen im Untersuchungszeitraum von sechs Jahren in mindestens einem Jahr einen Substanzverzehr erfährt. Der Vermögensteuer kommt somit keinesfalls der vielfach postulierte Charakter einer eher mäßig belastenden und im Wesentlichen substanzverschonenden Steuer zu. Zusatzbelastungen von knapp 100 bis zu 300% der Ertragsteuerlast sind keine Seltenheit und veranschaulichen das Gefährdungspotenzial dieser Steuer für den Wirtschaftsstandort Deutschland.
Keywords: Steuerbelastung; Substanzbesteuerung; ungleiche Vermögensverteilung; Veranlagungssimulation; Vermögensteuer

Editorial: What Is and What Is Not a Substantial Contribution? - Albers, Sönke; Sureth-Sloane, Caren (Business Research)

Can the CCCTB Alleviate Tax Discrimination against Loss-Making European Multinational Groups? - Ortmann, Regina; Sureth-Sloane, Caren

Can Tax Rate Increases Foster Investment Under Entry and Exit Flexibility? - Insights from an Economic Experiment - Fahr, Rene; Janssen, Elmar A.; Sureth-Sloane, Caren